Impact of Various Ovulation Synchronization Protocols on Serum Triglycerides and Cholesterol Profile in Repeat Breeder Cows during Different Breeding Seasons - Manokaran, Sakthivelu; Napolean, Rayappan E.; Selvaraju, Mani; Balasubramaniam, Gurusamipalyam A.; Palanisamy, Mahakrishnan; Geetha, Thangavel (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study evaluated whether various ovulation synchronization protocols modulate cholesterol and triglycerides profile andenhance fertility in repeat breeding crossbred cows under field conditions. The study was conducted in 100 repeat breeder cows whichwere divided into five experimental groups, viz., Group I, II, III, IV (Treatment groups) and Group V (Control group) during the highbreeding season (HBS: i.e., from October to March) and low breeding season (LBS: i.e., from April to September). Fifty cows were usedduring HBS and 50 cows during LBS. The Ovsynch, Presynch+Ovsynch, Ovsynch+Post-AI GnRH, and Ovsynch+Vitamin A protocols werefollowed to treat the Group I, II, III, and IV cows, respectively, and artificial insemination was performed during induced estrus. The groupV cows were inseminated during observed estrus. There was an increasing trend in cholesterol concentration from selection to 7 dayspost-AI in all the groups in both HBS and LBS. Further, the cholesterol concentration was higher during HBS than LBS. The pregnantcows had significantly (p
Keywords: Cholesterol; Repeat breeder cows; Season; Synchronization of ovulation; Triglycerides